2021
DOI: 10.1186/s12909-021-02734-4
|View full text |Cite
|
Sign up to set email alerts
|

How medical students cope with stress: a cross-sectional look at strategies and their sociodemographic antecedents

Abstract: Background Medical training can be highly stressful for students and negatively impact their mental health. Important to this matter are the types of coping strategies (and their antecedents) medical students use, which are only characterized to a limited extent. A better understanding of these phenomena can shed additional light on ways to support the health and well-being of medical students. Accordingly, we sought to determine medical students’ use of various coping reactions to stress and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 73 publications
(133 reference statements)
3
17
0
Order By: Relevance
“…4 Indeed, there is a growing body of evidence supporting that the further medical students get in their education, the more emotionally taxing it might be. 48 49 This pattern in medical education literature aligns with the observations of the present study where emotional coping styles were used relatively more commonly by the clinical students as compared with another group, while findings revealed by Bamuhair et al 22 were inconsistent with this notion. However, a significant positive correlation between psychological morbidities and PEC and PPC scores in clinical years indicates that coping styles adopted by students at a very challenging stage of medical education were not satisfactory and predicts stress in long term.…”
Section: Discussionsupporting
confidence: 90%
“…4 Indeed, there is a growing body of evidence supporting that the further medical students get in their education, the more emotionally taxing it might be. 48 49 This pattern in medical education literature aligns with the observations of the present study where emotional coping styles were used relatively more commonly by the clinical students as compared with another group, while findings revealed by Bamuhair et al 22 were inconsistent with this notion. However, a significant positive correlation between psychological morbidities and PEC and PPC scores in clinical years indicates that coping styles adopted by students at a very challenging stage of medical education were not satisfactory and predicts stress in long term.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding gender differences, in a COVID-19 situation, a May 2021 study by Neufeld et al showed that females reported greater use of behavioral disengagement, while men reported less trust in emotional and instrumental support [61]. The literature suggests that differences in coping with stress may be due to playing gender roles [62].…”
Section: Discussionmentioning
confidence: 99%
“…Females are more prone to depression and related symptoms compared to men ( 29 ). Abnormal menstruation further adds to the existing high stress among the medical students due to voluminous curricular content ( 30 33 ). A study of 414 medical students reported positive correlation between PMS and anxiety, depression, and stress.…”
Section: Introductionmentioning
confidence: 99%